Benthic foraminifera and ostracoda in ODP Hole 107-650A - Hieke, Werner; Glacon, Georgette; Hasegawa, Shiro; Müller, Carla; Peypouquet, Jean Pierre (Supplement to: Hieke, W et al. (1990): Sedimentation in the Marsili Basin during Quaternary (ODP Site 650, Tyrrhenian Sea). In: Kastens, KA; Mascle, J; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 107, 255-289, https://doi.org/10.2973/odp.proc.sr.107.120.1990, 1990)
Twenty-three sediment intervals from top of Site 650 down to 510 m below seafloor have been studied. Their thicknesses vary between 0.25 m and about 40 m. The studied deposits are turbidites or parts of them except one which is interpreted as an ash-fall layer. The composition of the turbidites signalizes sources from shallow water/coastal areas as well as from deep water levels. Repeated mobilization and displacement seems to have been common. Volcaniclastic material is the dominant component of the whole studied part of Site 650 sedimentary sequence. Ashfall deposits as well as normal open marine sediments are rare.